Hypercholesterolaemia and vascular dementia - Appleton, Jason P.; Scutt, Polly; Sprigg, Nikola; Bath, Philip M.W. (Portland Press, 2017)
Vascular dementia (VaD) is the second commonest cause of dementia. Stroke is the leading cause of disability in adults in developed countries, the second major cause of dementia and the third commonest cause of death. Traditional vascular risk factors–diabetes, hypercholesterolaemia, hypertension and smoking–are implicated as risk factors for VaD. The associations between cholesterol and small vessel disease (SVD), stroke, cognitive impairment and subsequent dementia are complex and as yet not fully understood. Similarly, the effects of lipids and lipid-lowering therapy on preventing or treating dementia remain unclear; the few trials that have assessed lipid-lowering therapy for preventing (two trials) or treating (four trials) dementia found no evidence to support the use of lipid-lowering therapy for these indications. It is appropriate to treat those patients with vascular risk factors that meet criteria for lipid-lowering therapy for the primary and secondary prevention of cardiovascular and cerebrovascular events, and in line with current guidelines. Managing the individual patient in a holistic manner according to his or her own vascular risk profile is recommended. Although the paucity of randomized controlled evidence makes for challenging clinical decision making, it provides multiple opportunities for on-going and future research, as discussed here.